Training transfer in elite distance running: from theory to practical application - Nurmekivi, A.; Lemberg, H. (New Studies in Athletics, 2012)
Successful training for endurance running events depends on the optimal connection of training exercises and the transfer of training effects. Not every stimulus will automatically lead to an improvement in running performance. This survey examines the optimal connection of endurance and strength properties and training transfer in the annual training cycle of elite distance runners, applying a logical - analytical approach. The empirical experience of successful coaches confirms contemporary scientific reseach, which tells us that if the effect of endurance and strength exercises is directed at the some muscle fibres - to slow - twitch fibres during the preparatory period and twitch lla fibres during preparation for competitions - then reciprocal relations between them do not emerge and the training trasfer will be efficient. The logical sequences of developing motor abilities in an annual training cycle, recommended by different authors, provide ideas for programming an individually suited training pattern of a endurance runner, bearing in mind the positive transfer of training.